Development, Feasibility, and Student Feedback on CAI-Based Learning Media: A Case Study in Web Programming Courses - Wahyu Hanaldi; Pipit Puspitasari (LPPM Universitas Andalas, 2026)
We evaluated the feasibility of Computer-Assisted Instruction (CAI) based learning media and measured student responses in the Informatics Study Program. We conducted an experiment involving 21 students who had various academic abilities. Our assessment is based on three criteria: method of use, material content, media appearance, and ease of use. The research results show that CAI media is suitable for use. In the method of use, we get a percentage of 72.6%, which is quite significant. CAI media received a score of 76.5% in the material content aspect, which is included in the outstanding category. Media views obtained 76.6% and were also included in the exceptional category. Meanwhile, the ease-of-use aspect received the highest score, 79.9%, in the outstanding category. Overall, we conclude that CAI-based learning media is effective and suitable for use as a tool in the learning process in the Informatics Study Program.